Change in microcalcifications on mammography after neoadjuvant chemotherapy in breast cancer patients: correlation with tumor response grade and comparison with lesion extent. (February 2019) - Yim, Hyunee; Ha, Taeyang; Kang, Doo Kyoung; Park, Seong Young; Jung, Yongsik; Kim, Tae Hee
Background: After neoadjuvant chemotherapy (NAC), persistent microcalcifications are often observed in spite of a decrease in the primary tumor size. Purpose: To analyze the changes in microcalcifications after NAC and to evaluate the accuracy of residual microcalcifications in predicting the extent of residual cancer. Material and Methods: Eighty patients who received NAC and underwent both mammography and magnetic resonance imaging (MRI) before and after the completion of NAC were included. The location of microcalcifications was classified into two types: inside the mass and outside the mass. Results: The extent of the residual calcifications was larger than the pathologic residual lesion in 14 (74%) of 19 patients with complete response (CR) on MRI, but the discrepancy was <1 cm in eight (42%) patients. The median value of the discrepancy was significantly higher in patients showing CR with outside calcifications compared to CR with inside calcifications (2.0 cm vs. 0.7 cm, P  = 0.008). After NAC, the decrease of calcifications was more frequently observed in cancers showing CR on MRI or Miller-Payne grade 5 and the increase of calcifications more frequently occurred in cancers showing progress disease on MRI or Miller-Payne grade 1 ( P  < 0.001 and P  = 0.044). Conclusion: The change in microcalcifications after NAC was correlated with the tumor response to NAC. The discrepancy was highest in the group showing CR on MRI with outside calcifications. In tumors with inside calcifications, the discrepancy was relatively low within an acceptable range.